The cyclical position of housing prices: A VECM approach for Hungary - Tamás Berki; Tibor Szendrei (Magyar Nemzeti Bank, 2017)
This paper aims to estimate a long-term equilibrium price level for the Hungarian housing market by identifying key underlying macroeconomic factors. For this, in line with the empirical literature, a vector error correction model is employed. The housing market price level is mapped by the newly established MNB housing price index. The results establish one stable cointegrating relationship between the housing prices and its longterm driving factors: average new housing loans, disposable income and housing stock. Credit channel plays a decisive role in determining equilibrium level of housing prices. Housing prices exhibit overshooting to various shocks potentially due to the protracted supply side adjustment. Due to the short sample size the estimated price gap might be underestimated in magnitude; nevertheless the fairly slow price adjustment coefficient ensures a persistent gap. Therefore, the sign of the estimated price gap is informative for policy makers from a macroprudential perspective.
Keywords: E44; R21; R31; 330; housing prices; VECM; error correction; housing loans; cyclical position